Using HDF5 as best practices for a business intelligence initiative - Pombeiro, Tiago Cardoso Pereira Fialho (2017)
Internship Report presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence